Hope, never fear : a personal portrait of the Obamas - Shell, Callie, 1961-; Obama, Barack; Obama, Michelle, 1964- (Chronicle Books, in association with Blackwell & Ruth, 2019)
"Award-winning photographer Callie Shell presents an intimate and moving portrait of Barack and Michelle Obama and the presidency that made history. This unique look behind the curtains follows the journey from the Obama's home in Chicago to the White House with a collection of nearly 200 photographs, each combined with inspiring and revealing quotes from Michelle and Barack that reveal their warmth, compassion, and unending commitment to service. With an in-depth introduction by Shell, together with notes drawn from the detailed diaries she kept during her time with the Obamas, this is a deeply personal insight into this extraordinary couple who inspired and empowered millions of people."--Publisher.